Between Social Media and Social Capital: Synergizing Algorithms and Gotong Royong in Digital-Based Tourism Promotion in Penglipuran Village - Bagus Putu Wahyu Nirmala; I Made Darsana (Mandalika Institute, 2023)
Abstract: In the Tourism 4.0 era, social media algorithms play an important role in determining the visibility of tourism destinations. This study examines how social capital, through trust, norms, and social networks, supports collective digital action in promoting Penglipuran Village, Bali. Using an exploratory qualitative case study approach, the research explores how the local community appropriates digital technology to strengthen tourism promotion. The findings show that strong relational trust encourages residents to voluntarily engage in activities such as liking, sharing, and promoting village-related content, which helps increase visibility on social media platforms. Community norms rooted in the Tri Hita Karana philosophy ensure that digital promotion remains authentic and culturally appropriate, while social networks facilitate coordinated online participation. The study also finds that the community adapts traditional gotong royong practices into organized digital creative activities, demonstrating strong dynamic capabilities in responding to technological change. These processes contribute to a collaborative tourism promotion model involving residents, tourists, and other stakeholders. The study concludes that successful digital transformation in tourism villages depends not only on technological infrastructure but also on the effective mobilization and reconfiguration of social capital.